More marginalization, less career development? Linking marginalization profiles to decent work among rural teachers - Jiajian Wang; Biru Chang (Acta Psychologica)
Abstracts: Using Latent Profile Analysis, this study explored the connections between different marginalization profiles and perceptions of decent work among rural primary school teachers in China. Analyzing data from 443 teachers across seven rural primary schools in Fujian Province, we discerned three unique marginalization profiles: Robust Adapters (n = 182, 41 %), Challenge Facers (n = 210, 47 %), and Conditioned Survivors (n = 51, 12 %). These profiles were examined for their links to decent work dimensions. Findings indicated that the Robust Adapters significantly outperformed both the Challenge Facers and Conditioned Survivors across all five dimensions of decent work. In contrast, there were no significant differences between the performances of the Challenge Facers and Conditioned Survivors in these dimensions, which indicated that more marginalization was not inevitably linked to less decent work. The study concluded by discussing the implications of these findings and the directions of future research.